BIEN JURÍDICO, CORRUPCIÓN PÚBLICA, ABUSO, GESTIÓN Y OPORTUNIDAD EN LOS DELITOS CONTRA LA ADMINISTRACIÓN PÚBLICA EN EL PERÚ - Vílchez Chinchayán, Ronald (Revista de Derecho, 2022)
The author approaches the study of endangerment crimes, considering the problems that surround them. He points out that difficulties arise both at an external (legitimacy) and internal (configuration) level. In both cases there is a need to review the proposals or suggest new ways to solve them. For this reason, it reviews the evolution of the crimes, from its “non-existence”, passing through its recognition as an exceptional figure, up to its location as a classification of its own and with special characteristics. Even with the intent of the doctrine and the numerous proposals remain outstanding issues and many unknowns to be resolved.